2014
DOI: 10.1287/opre.2014.1260
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Scrip Systems

Abstract: Scrip systems provide a non-monetary trade economy for exchange of resources. We model a scrip system as a stochastic game and study system design issues on selection rules to match potential trade partners over time. We show the optimality of one particular rule in terms of maximizing social welfare for a given scrip system that guarantees players' incentives to participate. We also investigate the optimal number of scrips to issue under this rule. In particular, if the time discount factor is close enough to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…79 In this connection, there is often information about both when currently available donors will no longer be available and when donors who are not currently available will become available. 80 See, for example, Möbius (2001), Hauser and Hopenhayn (2008), Johnson et al (2014), andKash et al (2015) for literature on scrip systems and trading favors in dynamic games. 81 The main idea relies on the power of two choices in computer science (Mitzenmacher 2001), which allows creating the desired drift in the credits of each hospital.…”
Section: Endnotesmentioning
confidence: 99%
“…79 In this connection, there is often information about both when currently available donors will no longer be available and when donors who are not currently available will become available. 80 See, for example, Möbius (2001), Hauser and Hopenhayn (2008), Johnson et al (2014), andKash et al (2015) for literature on scrip systems and trading favors in dynamic games. 81 The main idea relies on the power of two choices in computer science (Mitzenmacher 2001), which allows creating the desired drift in the credits of each hospital.…”
Section: Endnotesmentioning
confidence: 99%
“…Other work has shown that changing the random volunteer procedure can improve welfare [Johnson et al, 2014] and that this approach still works if more than one agent must be hired to perform work [Humbert et al, 2011]. Work from the systems community has looked at practical details such as the efficient implementation of a token bank [Vishnumurthy et al, 2003].…”
Section: Related Workmentioning
confidence: 99%
“…They associate a price (in bandwidth) with each file and find a market equilibrium in the resulting economy. Later work by Aperjis et al does use a currency, but the focus remains on establishing market prices [2008] Subsequent to our work, Dandekar et al [2011] examined networks where each agent can issue his own scrip, Rahman et al [2010] proposed a protocol to automatically adjust credit policies to maintain stability, Humbert et al [2011] modeled scrip systems where multiple agents combine to provide service, van der Schaar et al [2013] studied how to set parameters in a way that is robust to noise, and Johnson et al [2014] showed that welfare can be improved if the system prefers volunteers with low amounts of scrip.…”
Section: Related Workmentioning
confidence: 99%
“…If there is at least one volunteer, someone is chosen from among the volunteers (at random) to satisfy the request. Our model allows some agents to be more likely to be chosen (perhaps they have more bandwidth) but does not capture rules that take the amount of scrip volunteers have into account (such rules are considered by Johnson et al [2014]) or allow an agent to specify which agent is chosen. Allowing agents this type of control would break the symmetries we use to characterize the long-run behavior of the system, and would create new opportunities for strategic behavior.…”
Section: The Modelmentioning
confidence: 99%